Binder-less chemical grafting of SiO2 nanoparticles onto polyethylene separators for lithium-ion batteries - Na, Wonjun; Koh, Ki Hwan; Lee, Albert S.; Cho, Sangho; Ok, Byoeri; Hwang, Suk-Won; Lee, Jin Hong; Koo, Chong Min (ELSEVIER, 2019)
Silica nanoparticles were chemically grafted onto a porous polyethylene separator to improve the adhesion strength, thermal stability, and electrochemical performance of a polyolefin separator. A surface activation via UVO plasma treatment, followed by silane hybridization yielded a polymeric binder-free, thin coating of SiO2 nanoparticles onto the separator. The chemical grafting provided a much stronger adhesive strength (> 2.5 N/cm), reduced thermal shrinkage (< 5% at 120 degrees C), and higher ionic conductivity (0.84 mS/cm) than conventional physical coating of a ceramic particle-based polymer composite. Lithium-ion batteries fabricated with metallic lithium as the anode, a LiFePO4 (LFP) cathode and SiO2-grafted separator showed an excellent rate capability (68 mAh/g at 5 C) and cycling performance (143 mAh/g after 200 cycles).
Keywords: HYBRID IONOGEL ELECTROLYTES; ATOMIC LAYER DEPOSITION; POLYMER ELECTROLYTES; COMPOSITE MEMBRANE; CYCLING STABILITY; CHALLENGES